EPIDEMIOLOGICAL PROFILE OF EDENTULISM AND ORAL REHABILITATIONS WITH DENTAL IMPLANTS IN A BRAZILIAN ADULT SUBPOPULATION (CIPEEX, 2025)
The epidemiological aspects of edentulism and rehabilitation with dental implants were evaluated in an adult population from Central Brazil. Panoramic radiographs were analyzed, and data regarding sex, age at the time of examination, number of missing teeth, and number and location of dental implants were collected. Statistical significance was determined using the Chi-square test. The study involved 672 female patients (59.5%) and 457 male patients (40.5%), aged between 22 and 80 years (mean = 47.7 years). A total of 67.5% (n = 762) of the sample was partially edentulous, 30.5% (n = 344) was dentate, and 2.0% (n = 23) was completely edentulous. A total of 6,202 teeth were missing, of which 3,461 (55.8%) were maxillary teeth and 4,709 (76%) were posterior teeth. The most frequently missing tooth was the lower right first molar (n = 549; 8.85%). Statistical differences between the type of missing tooth and sex were recorded only for teeth 17 (P = 0.030), 26 (P = 0.014), and 37 (P = 0.012). A total of 188 patients (16.7%) had oral rehabilitations with dental implants, totaling 664 installed implants. Of these, 268 (40.4%) implants were located in the posterior region of the mandible, while 176 (26.5%) were located in the posterior region of the maxilla. The adult population of Central Brazil presents a high number of missing teeth and a reduced number of rehabilitations involving the placement of dental implants.
Keywords: Edentulism; tooth loss; dental implants; panoramic radiography